The Value of Visfatin in the Prediction of Metabolic Syndrome: A Systematic Review and Meta-Analysis - Jiang, Yingling; Zhou, Lihua (Hormone and Metabolic Research, 2023)
Various studies have shown that visfatin may be connected to metabolic syndrome (MS). However, epidemiological studies yielded conflicting outcomes. The purpose of this article was to highlight the relationship between the plasma visfatin level and MS risk by conducting a meta-analysis of available literature. A comprehensive literature search of eligible studies was done up to January 2023. Data were presented as standard mean difference (SMD). Observational methodological meta-analysis was conducted to assess the relationships between visfatin levels and MS. The visfatin levels between patients with MS or not were calculated by SMD and 95% confidence interval (CI) using the random-effects model. Funnel plot (visually inspect publication bias), Egger’s linear regression test and Begger’s linear regression test were applied to describe the risk of publication bias. A sensitivity analysis was performed via sequentially omitting each of the study one by one. In total, 16 eligible studies comprising 1016 cases and 1414 healthy controls finally enrolled in the current meta-analysis for pooling meta-analysis. Overall, the meta-analysis results revealed that visfatin levels in MS patients were significantly greater than that of controls group (SMD: 0.60, 95% CI=0.18–1.03, I2=95%, p<0.001). The results of the subgroup analysis showed that gender did not affect the results of meta-analysis. This meta-analysis shed light on the fact that circulating visfatin levels were significantly higher in patients with MS than in the controls group. Visfatin may a chance to predict the occurrence of MS.
Keywords: visfatin; metabolic syndrome; meta-analysis